The discovery of a radio halo in PLCK G147.3-16.6 at Z = 0.65 - Van Weeren, R.; Intema, Hubertus; Lal, D.; Bonafede, A.; Jones, C.; Forman, W.; Röttgering, H.; Brüggen, M.; Stroe, A.; Hoeft, M.; Nuza, S.; De Gasperin, F. (Institute of Physics Publishing, 2014)
Recent X-ray and Sunyaev-Zel'dovich (SZ) observations have dramatically increased the number of known distant galaxy clusters. In some merging, low-redshift (z < 0.4) clusters, centrally located, diffuse, extended radio emission (radio halos) has been found. Using the Giant Metrewave Radio Telescope (GMRT), we report the detection of diffuse radio emission in the binary-merging cluster PLCK G147.3-16.6 located at z = 0.65. We classify the emission as a giant radio halo due to its large physical extent of about 0.9 Mpc and its low-surface brightness. We measure an integrated flux density of 7.3 ± 1.1 mJy at 610 MHz for the radio halo, resulting in a 1.4 GHz radio power of 5.1 × 1024 W Hz-1. The radio halo power is consistent with that expected from the known correlation between X-ray luminosity or the cluster integrated SZ signal and radio power. Our observations also suggest that more of these distant radio halos could be discovered with the GMRT.